The Effect of Food Quality and Perceived Value on Behavioral Intention Using Customer Satisfaction as A Mediation Variable (Study On Gacoan Noodle Restaurant in Surabaya) - Nadhifah Citra Tsani Soraya; Sudarmiatin Sudarmiatin; Titis Shinta Dhewi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The development of the food & beverage industry has recorded quite good growth in recent years due to the presence of the digital world. The purpose of this analysis is to determine the direct and indirect effects of food quality and perceived value on behavioral intentions through customer satisfaction at Mie Gacoan restaurants in Surabaya. The quantitative research model uses a sample of 273 respondents, with the main characteristics being consumers who make purchases at the Mie Gacoan restaurant in Surabaya using Online Food Delivery (OFD). This study uses descriptive analysis techniques, SEM-PLS and mediation tests. The research results show that food quality (X1) has a positive and significant effect on customer satisfaction (Z). Perceived value (X2) has a positive and significant effect on customer satisfaction (Z). Food quality (X1) has a positive and insignificant effect on behavioral intentions (Y). Perceived value (X2) has a positive and significant effect on behavioral intentions (Y). Customer satisfaction (Z) has a positive and significant effect on behavioral intentions (Y). Customer satisfaction (Z) has a positive and significant effect mediating food quality (X1) on behavioral intentions (Y). Customer satisfaction (Z) has a positive and significant effect mediating Perceived value (X2) on behavioral intentions (Y).